The Effect of a Music Program on Phonological Awareness in Preschoolers - Degé, Franziska; Schwarzer, Gudrun (Frontiers in Psychology, 2011)
The present experiment investigated the effect of a music program on phonological awareness in preschoolers. In particular, the effects of a music program and a phonological skills program on phonological awareness were compared. If language and music share basic processing mechanisms, the effect of both programs on enhancing phonological awareness should be similar. Forty-one preschoolers (22 boys) were randomly assigned to a phonological skills program, a music program, and a control group that received sports training (from which no effect was expected). Preschoolers were trained for 10 min on a daily basis over a period of 20 weeks. In a pretest, no differences were found between the three groups in regard to age, gender, intelligence, socioeconomic status, and phonological awareness. Children in the phonological skills group and the music group showed significant increases in phonological awareness from pre- to post-test. The children in the sports group did not show a significant increase from pre- to post-test. The enhancement of phonological awareness was basically driven by positive effects of the music program and the phonological skills program on phonological awareness for large phonological units. The data suggests that phonological awareness can be trained with a phonological skills program as well as a music program. These results can be interpreted as evidence of a shared sound category learning mechanism for language and music at preschool age.